2010
DOI: 10.1111/j.1365-2036.2010.04511.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: high-dose acid suppression for chronic cough - a double-blind, placebo-controlled study

Abstract: Summary Background Cough may be a manifestation of gastro-esophageal reflux disease (GERD). The utility of acid suppression in GERD-related cough is uncertain. Aim To assess the impact of high-dose acid suppression with proton pump inhibitors (PPI) on chronic cough in subjects with rare or no heartburn. Methods Subjects were non-smokers without history of asthma, with chronic cough for > 8 weeks. All subjects underwent a baseline 24 hr pH/impedance study, methacholine challenge test (MCT), and laryngoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 43 publications
2
127
1
3
Order By: Relevance
“…Two recent, double-blind, placebo-controlled trials in adult patients with chronic cough did not demonstrate that PPIs are more effective than placebo. 67,68 A recent metaanalysis of 5 randomized, placebo-controlled trials in adult patients with chronic cough did not find sufficient evidence in favor of PPI therapy. 69 Hoarseness has also been considered to be an important extraesophageal manifestation of GERD.…”
Section: Extraesophageal M Anifestations Of Gastroesophageal Reflux Dmentioning
confidence: 99%
“…Two recent, double-blind, placebo-controlled trials in adult patients with chronic cough did not demonstrate that PPIs are more effective than placebo. 67,68 A recent metaanalysis of 5 randomized, placebo-controlled trials in adult patients with chronic cough did not find sufficient evidence in favor of PPI therapy. 69 Hoarseness has also been considered to be an important extraesophageal manifestation of GERD.…”
Section: Extraesophageal M Anifestations Of Gastroesophageal Reflux Dmentioning
confidence: 99%
“…36 No benefits on cough severity or quality of life were observed, suggesting that there was no evidence that the chronic cough was due to acid reflux with GERD. Moreover, there were no serious adverse events, and no one was withdrawn from the study for safety.…”
Section: Inhaled Corticosteroids (Ics): This Strategy Targetsmentioning
confidence: 95%
“…Asthma was excluded by physician Idiopathic chronic cough 1 study 20,25 1 SR 32 Chronic cough of unknown etiology 3 studies 26,36,37 Chronic treatment-resistant cough 1 study 25 Intractable chronic cough 1 study 25 Postviral vagal neuropathy 1 study 22 SR ÂŒ systematic review.…”
mentioning
confidence: 99%
“…A systematic review found no conclusive support for the use of PPIs in reflux cough [54]. More recently, two randomised controlled trials confirmed little or no effect of PPIs on chronic cough when compared with placebo (placebo, as is common in the trials of cough, having quite a marked effect over baseline) [55,56]. The authors of these trial reports [55,56] concluded that, given the evidence that PPIs may increase the likelihood of aspiration pneumonia [57], PPIs should not be routinely used in the treatment of a reflux cough, but should be reserved for patients exhibiting features of acid-related disease [58] or bronchospasm [59] in addition to cough.…”
Section: Cough and Refluxmentioning
confidence: 99%